2004
DOI: 10.1051/0004-6361:20040116
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene glycol in comet C/1995 O1 (Hale-Bopp)

Abstract: Abstract.We report the detection of ethylene glycol (HOCH 2 CH 2 OH) in comet C/1995 O1 (Hale-Bopp) from the analysis of archival radio spectra. Its production rate is ≈0.25% that of water, making it one of the most abundant organic molecules in cometary ices. This detection strengthens the similarity between interstellar and cometary material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 18 publications
3
94
0
Order By: Relevance
“…It is important to decipher the role of grain-surface chemistry and radiation processing versus gas-phase chemistry (Walsh et al 2014). As discussed by Crovisier et al (2004a) and Walsh et al (2014), an important issue is the now confirmed high abundance of ethylene glycol in comets, which is at least 5-6 times higher than that of the chemically related species CH 2 OHCHO (glycolaldehyde) ( Table 3). By contrast, both molecules are observed in similar abundances in the hot core Sgr B2(N) (Hollis et al 2002), and tentatively in the Class 0 solar-type binary protostar IRAS 16293-2422, where ethylene glycol relative to glycolaldehyde is 0.3-0.5 (Jørgensen et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to decipher the role of grain-surface chemistry and radiation processing versus gas-phase chemistry (Walsh et al 2014). As discussed by Crovisier et al (2004a) and Walsh et al (2014), an important issue is the now confirmed high abundance of ethylene glycol in comets, which is at least 5-6 times higher than that of the chemically related species CH 2 OHCHO (glycolaldehyde) ( Table 3). By contrast, both molecules are observed in similar abundances in the hot core Sgr B2(N) (Hollis et al 2002), and tentatively in the Class 0 solar-type binary protostar IRAS 16293-2422, where ethylene glycol relative to glycolaldehyde is 0.3-0.5 (Jørgensen et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We report here the detection of ethylene glycol (CH 2 OH) 2 and formamide (NH 2 CHO) in comets C/2012 F6 (Lemmon) (hereafter referred to as Lemmon) and C/2013 R1 (Lovejoy) (hereafter Lovejoy), for the first time since their discovery in comet C/1995 O1 (Hale-Bopp) (Crovisier et al 2004a;Bockelée-Morvan et al 2000). We also present the detection of Based on observations carried out with the IRAM 30 m telescope.…”
Section: Introductionmentioning
confidence: 89%
“…Very recently, it was also detected in the hot corinos associated with the class 0 protostars NGC 1333-IRAS2A (Maury et al 2014) and, tentatively, IRAS 16293-2422B (Jørgensen et al 2012). Finally, ethanediol was also found to be abundant in the outflows of comet Hale-Bopp (Crovisier 2004).…”
Section: Introductionmentioning
confidence: 91%
“…To date, more than 20 parent molecules have been observed in cometary comae including the relatively complex species, H 2 CO, CH 3 OH, HCOOH, CH 3 CHO, HC 3 N, CH 3 CN, NH 2 CHO, HCOOCH 3 , and ethylene glycol ((HOCH 2 ) 2 ), which are relevant to this work. Of these species, CH 3 CHO, NH 2 CHO, HCOOCH 3 , and (HOCH 2 ) 2 have been observed in only a single object, comet Hale-Bopp, with percentage abundances of 0.02%, 0.015%, 0.08%, and 0.25% (relative to H 2 O), respectively (see, e.g., Bockelée-Morvan et al 2004;Crovisier et al 2004aCrovisier et al ,b, 2006Mumma & Charnley 2011).…”
Section: Complex Molecules In Cometsmentioning
confidence: 99%